La maison du jardinier - Annick Heitzmann (Bulletin du Centre de Recherche du Château de Versailles, 2008)
In 1749, Louis XV established a Menagerie (a collection of domesticated animals and other more exotic species) near the Château de Trianon. Together with this project, he planned a flower garden and asked the horticulturist Claude Richard to manage it and to reside at the Trianon. A house was built on the site of the plant nursery near the gardens for which Richard would be responsible. The order for this building was issued on 17 September 1750, and by October the cellars were being excavated. The main building was finished first, followed by a narrower building opposite. Between the two buildings was a trapezoidal courtyard, separated by a wall from a plant nursery. While the flower garden was being laid out, Richard was given permission in 1753 to erect several greenhouses. Numerous seeds and plants sent back by naturalists from their travels were acclimatised at the Trianon by Richard and his son Antoine. In 1773, the Richards were the head gardeners of the Menagerie de Trianon gardens, known by then as the ‘French Garden’ and the ‘Botanical Garden’. When Marie Antoinette took possession of the Petit Trianon the following year, she had the botanical garden cleared to make way for her first English garden. Her architect, Richard Mique, built new greenhouses near Richard’s house to provide the Hamlet with vegetables and flowers. After Claude and Antoine Richard, successive head gardeners lived in the house until about 1900. Today it is known as the Pavillon de Jussieu, after the botanist Bernard de Jussieu, whom the king hired in 1759 to oversee the development of the botanical garden. Jussieu worked with the Richards and no doubt stayed with them when he was visiting the Trianon.